Ovarian reaction and estrus manifestation in delayed puberty gilts after treatment with equine chorionic gonadotropin - Stančić Ivan B; Bošnjak Darko V; Radović Ivan B; Stančić Blagoje L; Harvey Roger B; Anderson Robin C (BMC, 2012)
Abstract Background Prolonged pre-insemination anestrus (i.e. delayed puberty) is a major contributing factor for culling up to 30% of the replacement gilts at large breeding farm units in Vojvodina. It is imperative to determine if these gilts are acyclic (prepubertal) or cyclic, but just fail to exhibit behavioural estrus. Recent investigations demonstrate that treatment with equine chorionic gonadotropin (eCG) can increase the diestrous phase duration in sexually mature gilts. Based on these finding, the aim of the present studies was to determine the reproductive status of delayed puberty gilts following injection with eCG. Methods Two experiments were conducted on a swine breeding farm in Vojvodina. In Exp. 1, 20 prepubertal (acyclic) gilts, and 120 sexually mature (cyclic) gilts were injected with a single injection of 400 IU eCG + 200 IU human chorionic gonadotropin (hCG) or with 1000 IU eCG (cyclic gilts), at d5, d11 or d17 after spontaneous estrus detection, to determine their ovarian reaction and induced estrus manifestation. In Exp. 2, sixty delayed puberty gilts (estrus not detected until 8 month of age, av. 258 days) were culled from breeding herd and slaughtered to determine their reproductive status based on ovarian anatomical features. The second group of gilts (n = 60) was treated with a single 1000 IU eCG injection to determine their reproductive status, based on the interval between eCG injection to estrus detection and duration. The data were analyzed by descriptive statistics, t-test, analysis of variance and Duncan's test in the software package Statistics 10th. Results Ovulations were induced in 90% of acyclic (sexually immature) and, on average, 93.3% of cyclic (sexually mature) gilts after the eCG injection. On average, 4 days after the eCG injection, estrus was detected in 85% of the treated acyclic (sexually immature) gilts and in 95% (19/20) of the cyclic (sexually mature) gilts, treated with eCG on day 17 after spontaneous estrus detection. The interval from eCG to induced estrus detection was prolonged (av. 25 days) in 95% (19/20) of the sexually mature gilts treated with eCG on day 5 and in 90% (18/20) of gilts treated on day 11 after spontaneous estrus detection (Exp. 1). Forty anestrous gilts reached cyclic pubertal ovarian activity. Estrus manifestation was detected in 56 gilts (93.3% of the total 60 treated prolonged anestrous gilts, av. 259 days of age), after a single 1000 IU eCG injection. Thirty-four gilts (60.7% of the total gilts in estrus) with prolonged eCG to estrus interval (av. 24.7 days) were considered spontaneously cyclic (sexually mature), but behaviourally anestrous before treatment. The remaining 22 (39.3% of the total gilts in estrus) were considered truly sexually immature (acyclic) before the treatment or were eCG injected in the late luteal or proestrous phase of spontaneous estrous cycle (Exp. 2). Conclusions In 66.7% of the delayed puberty gilts, pre-ovulatory follicles (PoF), corpora hemorrhagica (CH), corpora lutea (CL), or corpora albicantia (CA) were found on the ovaries upon post mortem examination. These gilts were considered as sexually mature before slaughtering. In 60.7% of the delayed puberty gilts, behavioural estrus was detected an average of 24.7 days following eCG injections. These gilts were considered as eCG treated during the luteal phase (diestrus) of the spontaneous estrus cycle. Both findings suggest that delayed puberty gilts actually reached cyclic pubertal ovarian activity (sexual maturity) before culling from the breeding herd.